1999
DOI: 10.1073/pnas.96.24.13685
|View full text |Cite
|
Sign up to set email alerts
|

Topoisomerase II drives DNA transport by hydrolyzing one ATP

Abstract: DNA topoisomerase II is a homodimeric molecular machine that couples ATP usage to the transport of one DNA segment through a transient break in another segment. In the presence of a nonhydrolyzable ATP analog, the enzyme is known to promote a single turnover of DNA transport. Current models for the enzyme's mechanism based on this result have hydrolysis of two ATPs as the last step, used only to reset the enzyme for another round of reaction. Using rapid-quench techniques, topoisomerase II recently was shown t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
128
2

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(141 citation statements)
references
References 30 publications
(45 reference statements)
11
128
2
Order By: Relevance
“…We suggest that, upon dimerization of the N-terminal gate, DNA cleavage and strand passage lead to hydrolysis of one ATP molecule, followed by release of ADP and P i . This is in accord with the observation of Lindsley and co-workers (40) that the ATP hydrolysis by the two subunits of the enzyme is sequential rather than simultaneous. The hydrolysis of the first ATP molecule does not lead to the dissociation of the N-terminal dimerization, but requires hydrolysis and release of the second bound ATP molecule.…”
Section: Discussionsupporting
confidence: 81%
“…We suggest that, upon dimerization of the N-terminal gate, DNA cleavage and strand passage lead to hydrolysis of one ATP molecule, followed by release of ADP and P i . This is in accord with the observation of Lindsley and co-workers (40) that the ATP hydrolysis by the two subunits of the enzyme is sequential rather than simultaneous. The hydrolysis of the first ATP molecule does not lead to the dissociation of the N-terminal dimerization, but requires hydrolysis and release of the second bound ATP molecule.…”
Section: Discussionsupporting
confidence: 81%
“…However, it is unlikely that phosphate release is the overall rate-limiting step for strand passage as single-molecule measurements of Drosophila Topo II indicate that a single tension-dependent, chirality-independent, rate-limiting step governs strand passage (24). Moreover, rapid kinetic measurements showed that ATP hydrolysis is at least 5-fold faster than the strand passage rate at saturating ATP (43). Tension-dependent unlinking measurements of htopo II␣ suggest a more complex relationship between strand passage and tension than was observed with Drosophila Topo II (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The rate-limiting step in the ATP hydrolysis cycle for yeast Topo II is the release of the first inorganic phosphate (42)(43)(44)(45)(46). However, it is unlikely that phosphate release is the overall rate-limiting step for strand passage as single-molecule measurements of Drosophila Topo II indicate that a single tension-dependent, chirality-independent, rate-limiting step governs strand passage (24).…”
Section: Discussionmentioning
confidence: 99%
“…Second, topoisomerase II uses the energy of adenosine triphosphate (ATP) to drive the overall DNA strand passage reaction [66,69,75,76]. While ATP is not required for either DNA cleavage or ligation, the binding of this nucleoside triphosphate triggers the translocation of DNA through the double-stranded nucleic acid gate [75,77]. ATP hydrolysis is necessary for enzyme recycling [66].…”
Section: Topoisomerase II Catalytic Cyclementioning
confidence: 99%
“…Normally, topoisomerase II binds two molecules of ATP [76]. Although ATP hydrolysis is not a prerequisite for the strand passage event, it appears that this step proceeds more rapidly if it is preceded by hydrolysis of one of the bound ATP molecules [77].…”
Section: Topoisomerase II Catalytic Cyclementioning
confidence: 99%